Study on the effect of the substrate material type and thickness on the performance of the filtering antenna design - Mohammed K. Alkhafaji; Hana’a A. Alhamadani; Yasir I. A. Al-Yasir; Ameer L. Saleh; Naser Ojaroudi Parchin; Raed A. Abd-Alhameed (Universitas Ahmad Dahlan, 2020)
This article presents a new design of a four-pole microstrip filtering antenna. The filtering antenna consists of a bandpass filter, which has four resonators integrated to a monopole patch antenna. The filtering antenna is designed with a relatively high bandwidth of about 1.22 GHz to satisfy a high-speed data transmission. Three types of dielectric substrate materials were used for the design of the filtering antenna, which is RT/Duroid 5880, RO3003, and FR-4. The simulation results of the filtering antenna design, which are established on the three different dielectric substrate materials, are done by using Computer Simulation Technology (CST) software. Comparison results of the filtering antenna that is established on the three different dielectric substrate materials are done at a fixed substrate height and different substrate heights. The filtering antenna is designed at a center frequency f0 = 2.412 GHz, which is suitable for WLAN applications.